A Game Oriented Approach for Teaching Computer Science - Clua, Esteban Walter Gonzalez (Anais do Workshop sobre Educação em Computação (WEI); 2008: Anais do XVI Workshop sobre Educação em Computação, 2008)
Introductory computer science courses should be altered to use attractive, engaging contexts. After defending this claim, the paper provides evidence that the context of computer games qualifies as both attractive and engaging. The heart of the paper is a description of how certain logical, mathematical, and algorithmic concepts fundamental to computing may be taught and learned within a game-oriented context. Tools and languages adequate for this purpose are briefly discussed. The author describes his initial experiences and observations in using this approach.